Landscape-driven phosphorus distribution and transformations in an intermittent river of semiarid Brazil - Silva, Antonio E. B.; Queiroz, Hermano M.; Oliveira, Daniel P.; Araujo Lopes, Giovanna Bergamim; Pereira, Tamara M.; Nóbrega, Gabriel N.; Barcellos, Diego; Rezende, Carla F.; Ferreira, Tiago O. (Frontiers in Water, 2026)
Intermittent rivers and ephemeral streams (IRES) are central to nutrient transport in semiarid regions, yet their role in phosphorus (P) dynamics under combined natural and anthropogenic pressures remains poorly understood. This study assessed sediments and surface waters along the Cruxati River Basin (Northeast Brazil), comparing upland, piedmont, and lowland zones. Field sampling included the following sediment parameters: pH, Eh, particle size distribution, total organic carbon (TOC), sequential P fractionation, and Fe forms. We also performed the following water analyses: pH, Eh, electrical conductivity (EC), dissolved oxygen (DO), total-P, and orthophosphate-P. Spatial characterization of land use/cover and trophic status of nearby reservoirs supported our environmental interpretations. Sediments were predominantly sandy (93.0 ± 7.2%), with kaolinite as the main mineral phase. Among the P fractions, oxide-P, silicate-P, and residual-P were dominant across the sites, while Ca-P was found only in the upland sites. Statistically significant differences were observed for silicate-P (0.0 ± 0.0 mg kg−1 upland; 15.2 ± 4.0 mg kg−1 piedmont; 29.4 ± 24.8 mg kg−1 lowland), Ca-P (14.4 ± 5.4 mg kg−1 upland; absent downstream), and residual-P (26.4 ± 16.8 mg kg−1 lowland vs. 8.1 ± 7.6 mg kg−1 piedmont). In surface waters, total-P decreased downstream (0.16 ± 0.03 mg L−1 upland; 0.07 ± 0.02 mg L−1 piedmont; 0.05 ± 0.0 mg L−1 lowland), whereas orthophosphate-P showed similar patterns across the sites. Land use mapping indicated >70% forest cover, 17% pasture, 8% agricultural mosaic, and 1% urban areas, with increasing fragmentation downstream. Reservoirs near the sampling zones were predominantly eutrophic, highlighting additional anthropogenic pressures. Our results revealed that P dynamics in IRES are shaped by the interaction between natural retention/release mechanisms and human-driven inputs, with depositional zones acting as critical hotspots. Our findings provide new insights into P cycling in semiarid IRES and their vulnerability under climate and land-use changes.